2019
DOI: 10.1128/iai.00369-19
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Kupffer Cells and Macrophages in Klebsiella pneumoniae-Induced Liver Abscess Disease

Abstract: Klebsiella pneumoniae-induced liver abscess (KLA) is emerging as a leading cause of pyogenic liver abscess worldwide. In recent years, the emergence of hypervirulent K. pneumoniae (hvKp) has been strongly associated with KLA. Unlike classical K. pneumoniae, which generally infects the immunocompromised population, hvKp can cause serious and invasive infections in young and healthy individuals. hvKp isolates are often associated with the K1/K2 capsular types and possess hypermucoviscous capsules. KLA is believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
(36 reference statements)
1
23
0
3
Order By: Relevance
“…Consistently, NP-HvKP/A and NP-HvKP/A2 exhibited reduced ability to adhere to the epithelial cells ( Figure 2(c,d )) or undergo phagocytosis by macrophage ( Figure 2(e )), as well as a lower chance of being killed by neutrophils ( Figure 3(b )). Our data is consistent with previous reports that HvKP exhibited lower phagocytosis by macrophage when compared to cKP strains [ 18 , 28 ]. However, another study reported that deletion of rmpA ( ∆rmpA ) in a HvKP strain, SGH10, exhibited no effect on uptake by RAW264.7 macrophages as well as adhesion to Caco-2 cells [ 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…Consistently, NP-HvKP/A and NP-HvKP/A2 exhibited reduced ability to adhere to the epithelial cells ( Figure 2(c,d )) or undergo phagocytosis by macrophage ( Figure 2(e )), as well as a lower chance of being killed by neutrophils ( Figure 3(b )). Our data is consistent with previous reports that HvKP exhibited lower phagocytosis by macrophage when compared to cKP strains [ 18 , 28 ]. However, another study reported that deletion of rmpA ( ∆rmpA ) in a HvKP strain, SGH10, exhibited no effect on uptake by RAW264.7 macrophages as well as adhesion to Caco-2 cells [ 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…These results suggested that liver abscesses cause a certain degree of immune inflammation. 44 An increase in ALT and AST, two sensitive markers indicating liver injury, was detected in K. pneumoniae -infected mice. It is worth mentioning that the levels of p-IκBα, nuclear NF-κB p65, and p50 subunits in the liver were significantly increased, suggesting the activation of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that it was reported the absolute numbers of Kupffer cells were quite constant except for a small increase during the 12h and 24h time points. 44 Different results may be related to different modeling methods, observation time points and experimental techniques. The current study also found that macrophagic infiltration promotes the rapid release of TNF-α, MCP-1, KC, and IP-10, amplifying the inflammatory cascade, finally leading to inflammatory storms.…”
Section: Discussionmentioning
confidence: 99%
“…characterized by a monomicrobial pyogenic liver abscess with or without extrahepatic seeding in the absence of previous biliary disease, intra-abdominal infection or recent intra-abdominal surgery [9,10]. The pathogen's source is generally the gastrointestinal tract and is acquired through fecal-oral transmission [11,12].…”
Section: Funding/conflict Of Interestmentioning
confidence: 99%
“…The pathogen's source is generally the gastrointestinal tract and is acquired through fecal-oral transmission [11,12]. After colonization, enteric bacteria are believed to translocate through the portal venous circulation [10] into the liver. Intestinal colonization may serve as a reservoir for pathogenic strains although evidence can be discordant [13,14] (Figure 3).…”
Section: Funding/conflict Of Interestmentioning
confidence: 99%